Pengaruh Literasi Digital, Kapabilitas Digital, dan Orientasi Kewirausahaan terhadap Kinerja Usaha UMKM Kuliner di Jakarta Barat - Sinta Fajri Utami; Fitra Dila Lestari; Suparno Suparno (Indo Publishing, 2026)
This study analyses the effect of digital literacy, digital capability, and entrepreneurial orientation on the business performance of culinary MSMEs in West Jakarta. The research is motivated by fluctuating income among culinary MSMEs during 2019–2024, where a high number of business units was not always accompanied by an even improvement in performance, as well as the generally low level of digital literacy and capability among MSME actors nationwide. A quantitative causal-associative approach was employed, with a population of 8,292 culinary MSMEs in West Jakarta and a sample of 170 respondents selected through purposive sampling. Primary data were collected via a 1–5 Likert-scale questionnaire, both online and offline, and analysed using multiple linear regression in SPSS. Instrument tests confirmed all items were valid and reliable, while classical assumption tests showed the data were normally distributed and free from multicollinearity and heteroscedasticity. Hypothesis testing showed that digital literacy, digital capability, and entrepreneurial orientation each had a positive and significant effect on business performance. Three variables explained 32.8% of the variation in performance. These findings underscore the importance of digital ability and entrepreneurial attitude in driving sales growth, profitability, and competitiveness among culinary MSMEs.